PERFORMANCE ANALYSIS OF A SPLIT TYPE ROOM AIR CONDITIONER (Jurnal Mekanikal, 2018)
This paper investigates the performance of a split room air conditioner in the special-purposelaboratory room. In order to evaluate the performance, an experimental set-up is constructed. The experimental components consist of a split room air conditioner which has, a hermeticcompressor, a condenser, an evaporator, capillary tube and two fans. For on-line readingpurposes , it uses data acquisition system and power meter. The unit is installed in the energyconservation laboratory with the room volume of 16.8 m' at Faculty of Engineering, UniversitiMalaya, Kuala Lumpur. Experimental result is obtained for various ambient temperatures. Theelectricity consumption and coefficient ofperformance ofthe system are measured and presented as a function ofthe ambient temperature.
Keywords: Keywords